Genetic insights and principal component analysis of inter-subspecific derivatives in rice (Oryza sativa L.) - Bonipas Antony, John; Saraswathi, Ramaswamy; Manonmani, Swaminathan; Ramalingam, Jedadeesan; Renganayaki, Perumalsamy Raju; Uma, Doraiswamy (Plant Science Today, 2025)
Rice is a staple crop in Southeast Asia and increasing its productivity through hybrid breeding is essential to meet the growing population demand. The development of new restorers is a key goal in hybrid rice breeding to increase heterosis. Studying newly developed breeding lines and their trait associations is crucial for their effective use in future breeding activities. The newly developed lines, derived from indica and tropical japonica crosses, were evaluated for eight quantitative traits across four locations to study genetic variation and trait associations. Single plant yield (20.92) had the highest genotypic coefficient of variation (CVg), while total spikelets per panicle (17.71), productive tillers (15.35) and plant height (13.31), recorded moderate CVg. Further, all traits except spikelet fertility, exhibited high broad-sense heritability spikelet fertility. The first three principal components (PCs), with eigenvalues greater than one, explained 67 % of the total variation. The biplot of the first two PCs, accounting for 53 % of the variation, showed significant divergence among genotypes, with plant height contributing most, followed by single plant yield and spikelet fertility. Spikelet fertility (0.44) and the total number of spikelets per panicle (0.25) showed a strong correlation with single plant yield in the combined analysis and across locations, making them promising traits for selection. Thus, greater emphasis must be placed on spikelet fertility and the number of spikelets per panicle when selecting inter-subspecific cross derivatives. The newly developed inter-subspecific breeding lines in the present study showed significant variation in yield and other traits, making them valuable resources for heterosis breeding.